3CAT-2: Attitude Determination and Control System for a GNSS-R Earth Observation 6U CubeSat Mission. Issue 1 (1st January 2016) - Cortiella, Alexandre; Vidal, David; Jané, Jaume; Juan, Enric; Olivé, Roger; Amézaga, Adrià; Munoz, Joan Francesc; Carreno-Luengo, Pol Via Hugo; Camps, Adriano
Abstract: This work describes the attitude determination and control system (ADCS) of 3 CAT-2, a six-unit CubeSat scheduled for launch this 2016. The ADCS of 3 CAT-2 aims at controlling the satellite in orbit and fulfilling the pointing requirements imposed by the mission. The attitude control system implemented in 3 CAT-2 will be used to point the antennas towards the Earth to perform altimetry tests, orient the solar panels towards the Sun to maximize power input when battery levels are critical, and reduce the tumbling motion of the satellite after the deployment phase. In order to guarantee pointing requirements for remote sensing purposes, an active three-axis attitude determination and control system is considered.